Analysis Of The Road Markings Reflectivity Service Life On Highways To Improve Safety - Oktopianto, Yogi; Rukman, Rukman (RSF Conference Series: Engineering and Technology, 2022)
Road markings can function for two years after installation. The maintenance and replacement program for highway markings aims to meet the established performance standards. Good visibility of the markings will help reduce the chances of traffic accidents. The problems are found in faded road markings along the segment during the service period. The research was conducted to investigate the change in reflectivity over time and to find a pattern of decreasing reflectivity in the service life during the design life. The research was conducted experimentally by making test objects. The reflectivity test at the existing location using a reflectometer is carried out periodically every two months. The results showed a pattern of decreasing the reflectivity of road markings during the 2-month service period by 2%, four months by 3%, six months by 6%, and eight months by 16%, and the pattern of declining marker reflectivity stops between 10 and 12 months. The maximum decrease occurred during the service period of 8 months, 16%. The age of markings on the highway cannot last for a service period of 2 years under actual conditions in the field. At the end of year 1, the average value was 242 mcd/m2/lux; this value is below the minimum required reflectivity of 250 mcd/m2/lux.